Dwight and the trilobite - Foster, Kelli C.; Erickson, Gina Clegg; Gifford, Kerri (Hauppauge, NY : Barron's, 1994)
Dwight and his mother Mrs. Knight go hunting for trilobites.
1.4
"A first book ages
Keywords: Trilobites -- Fiction; Stories in rhyme; Trilobites -- Fiction; Stories in rhyme